DECONSTRUCTING FALSE IDENTITY: EXPLORING GENDER DISCRIMINATION AND ROLE-PLAYING IN THE GIRL WHO TOUCHED THE STARS - Neeraj Sankhyan; Suman Sigroha (Celt: A Journal of Culture, English Language Teaching & Literature, 2015)
Mahesh Dattani, is an avant-garde Indian English dramatist known for his radical and unconventional dramatic themes. His plays are characterized by an extremely sensitive temperament that delves into the intricacies of the human nature and strives to expose the hypocrisy of the urban life and society. This paper discusses his play The Girl Who Touched the Stars as a quest for a lost identity. In doing so, the paper sheds light upon the underlying themes of gender discrimination, misogyny and role-playing that the playwright uses in this play to show how much these evils are rampant even amongst the educated classes of the society. Specifically, the paper explores the deconstruction of identity of the protagonist as employed by the playwright and examines the implications this technique has on the narrative of the play. The interconnection between the role-playing and the inherent theme of gender discrimination is also analyzed in order to see how these elements complement each other. Also, the paper comments on the efficacy of radio drama as a medium for handling a sensitive theme like this.